Perdamaian Sebagai Perwujudan Dalam Dialog Antar Agama - Aulia Aulia Agustin (Al-Mada: Jurnal Agama, Sosial, dan Budaya, 2018)
Indonesia is a pluralistic country with a variety of ethnicities, races, cultures, languages ​​and religions. Apart from being known as a pluralistic country, Indonesian people are also known to be very religious, and have made various efforts to create harmonious relations between religious communities. However, seeing the complex problems involving religious people in the current era is increasingly prevalent in this business as if in vain. Problems with a higher religion than religion that are no longer related to sadistic bandages, cruel, intolerant, even non-dialogical. Sam Harris, who is a new figure of atheism from the United States, also links this phenomenon and states that created religion creates conflict, division and social involvement. According to Sam, religion can support war, even religion is the core of the problem in the war. The war that was moved was justified because of religion, a religion that was often taken as a source of warfare. To realize the ideals of peace between religious communities, it is a significant effort to restore the nature of religion and the essential purpose of human life, dialogue is a form of effort. Dialogue with an inclusive dialogue model is a form of effort carried out in the present era. The strategy of implementing this dialogue model is one of the messages of religious peace in life, for the sake of religious and human safety. Interfaith dialogue is a form of support for each religious community and the support of the human race in racial struggle and struggle, conflict and inter-religious warfare. Dialogue The notion of interfaith is important as the goal of realizing a culture of peace and awareness will be responsible for virtue. Religious dialogue as a movement to call on all religious people to meet, make a strategy to build relationships between people on the basis of, compile, and coexist peacefully in different communities.